Deploying Smart Pipe in CDMA Network with PCC - Wei Zhou; Congjie Mao (Dianxin kexue)
PCC is the abbreviation of policy and charging control, which was introduced in 3GPP R7 and now it is in R12 stage. Policy control and flow based charging is the main function of PCC. The architecture, the main network elements of PCC deployed in CDMA network were introduced, and also some business scenarios were depicted. At last the evolution strategy of PCC from CDMA to LTE was provided.